Hera : the goddess and her glory - O'Connor, George (New York : First Second, 2011)
Introduces Hera, Zeus's wife and goddess of air, sky, and the heavens, and the only thing Zeus fears.
"A Neal Porter book."
"An imprint of Roaring Brook Press"--Colophon
Includes bibliographical references (page 76).
A Junior Library Guild selection
Accelerated Reader
Keywords: Hera -- (Greek deity) -- Comic books, strips, etc; Hera -- (Greek deity) -- Juvenile fiction; Mythology, Greek -- Comic books, strips, etc; Mythology, Greek -- Juvenile fiction; Hera -- (Greek deity) -- Cartoons and comics; Cartoons and comics; Mythologie grecque; Mythologie grecque -- Romans, nouvelles, etc. pour la jeunesse; Hera -- (Greek deity); Mythology, Greek; Hera (Greek deity); Greek mythology; Graphic novels; Cartoons and comics; Mythological comics; Juvenile works; Graphic novels; Fiction; Comics (Graphic works); Graphic novels; Graphic novels